2018
DOI: 10.1007/s00125-018-4549-7
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length is reduced in 9- to 16-year-old girls exposed to gestational diabetes in utero

Abstract: The 9- to 16-year-old girls of mothers with GDM had shorter telomeres than those from the control population. Further studies are needed to understand the extent to which shortened telomere length predicts and/or contributes to the increased risk of disease later in life among the offspring of women with GDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 54 publications
(61 reference statements)
2
26
1
Order By: Relevance
“…This is important to study, since TL at birth is a main predictor for TL throughout life ( 6 , 9 , 10 ), and TL later in life is associated with the risk of several outcomes, such as cancer and cardiovascular diseases ( 11 , 12 ). There is emerging evidence that factors such as maternal stress ( 13 , 14 ), inflammation ( 15 ), gestational diabetes ( 16 ), exposure to air pollution ( 17 , 18 ), tobacco smoke ( 19 ), and toxic metals ( 20 ) may influence offspring TL.…”
Section: Introductionmentioning
confidence: 99%
“…This is important to study, since TL at birth is a main predictor for TL throughout life ( 6 , 9 , 10 ), and TL later in life is associated with the risk of several outcomes, such as cancer and cardiovascular diseases ( 11 , 12 ). There is emerging evidence that factors such as maternal stress ( 13 , 14 ), inflammation ( 15 ), gestational diabetes ( 16 ), exposure to air pollution ( 17 , 18 ), tobacco smoke ( 19 ), and toxic metals ( 20 ) may influence offspring TL.…”
Section: Introductionmentioning
confidence: 99%
“…There is less information on maternal exposures in pregnancy and telomere length in children. A recent study (n = 439) demonstrated 14% shorter telomeres in 12-year-old children of mothers who had GDM, driven by shorter telomeres in female but not male children [38]. We demonstrated no effect modification with fetal sex, when assessing the metabolic syndrome and child telomere Table 3 Association between individual components of the metabolic syndrome in women during pregnancy, and increasing number of components, and child telomere length a length, though our sample size was small.…”
Section: Discussionmentioning
confidence: 51%
“…We have not shown, in this study, whether the shortened telomeres were inherited by the offspring. While some studies suggest that this is the case [16, 17], other studies find no such association [1820]. This may be due to the technical challenges imposed by the use of leukocyte DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, individuals may start life with shorter than normal telomeres that then play a role in the disease progression of diabetes [14], contributing to impaired glucose management and insulin secretion [15]. The latter possibility is indicated by the observation that diabetes during pregnancy, is linked to shortened telomere length in blood leukocytes from exposed children [16, 17], although not all studies report such a link [1820]. If individuals exposed in utero to GDM start life with shorter telomeres, this may explain why they are at higher risk of adverse outcomes such as T2DM later in life.…”
Section: Introductionmentioning
confidence: 99%